Las artesanías tradicionales y el turismo cultural en el cantón Babahoyo de la Provincia de Los Ríos - Estrada Torres, Katherine Lisbeth (2019)
The present investigation concerning traditional crafts and cultural tourism in the Babahoyo canton, province of Los Ríos, developed as a proposal to establish strategies to promote traditional crafts and cultural tourism of the Babahoyo canton, for which 87 artisans were surveyed. For the collection of information, a questionnaire was designed and developed containing nine questions, each with multiple answers. The selection of respondents was by random technique, considering the number required according to the formula proposed for the investigation. The theoretical distribution of frequencies was developed, in order to visibly appreciate the representative values of the sample using a pie chart. Based on the foregoing, it was determined that traditional handicrafts are a fundamental influence for cultural tourism and that it offers innumerable benefits for it, which is why its importance as a cultural manifestation within cultural tourism must be revalued and both promoted for its functioning and valid knowledge. ; In the Babahoyo canton it was evident that there is little diffusion or promotion of handicrafts, due to insufficient information on them, and the absence of contributions from the entities towards the cantonal cultural development and through strategies to promote dissemination of the handicrafts within the cultural tourism will be able to boost the knowledge of information, origin and cultural valuation of the same, in addition to achieving a boost in the cultural tourism of the canton